PERBANDINGAN HASIL BELAJAR MENGGUNAKAN SOFTWARE SIMULATION JARINGAN GNS3 DAN PACKET TRACER DALAM MENGATASI KETERBATASAN ALAT PADA KOMPETENSI WIDE AREA NETWORK (WAN) DI JURUSAN TKJ SMKS INFORMATIKA SUKMA MANDIRI - Ahmad Surahmat; masum masum (Teknik Informatika Fakultas Ilmu Komputer, 2019)
Problems in this research The media used in the teaching and learning process still has a shortage of the limited physical component in SMK Swasta Informatika Sukma Mandiri Cilegon. This study aims to determine the effect of the use of GNS3 on the results of learning network-based broad- based installation of students of class XI TKJ SMK Swasta Informatika Sukma Mandiri Cilegon. This type of research is experimental research. Class experiment I is class TKJ A using software simulation GNS3 and class experiment II is TKJ B using sotware simulation packet tracer. Technique of collecting data from post-test value, then analyzed for homogeneity test, normality test and hypothesis test. From the experimental class experimental I result I get the average value 78.77 and experiment II get average value 75, 42. The result of hypothesis calculation at significant level α = 0,05 got tcount> ttable (3,574> 1,688), because big tcount of ttable, null hypothesis (H0) rejected and alternative hypothesis (Ha) accepted. Thus, the hypothesis is accepted that there is a significant comparation to the student learning outcomes using Software GNS3 to the learning outcomes of installation of broad-based network devices on students of class XI TKJ SMK Swasta Informatika Sukma Mandiri Cilegon.